STRATEGI PEMASARAN PRODUK JASA KEUANGAN DI PERBANKAN SYARIAH DALAM PERSPEKTIF ISLAM - Alpajar Ramadhan; Muhammad Iqbal Fasa; Is Susanto (PT. Intelek Cendikiawan Nusantara, 2024)
This research discusses marketing strategies for financial service products in sharia banking from an Islamic perspective. The main focus of this research is the importance of applying ethics, honesty and transparency in every aspect of marketing. It was found that product innovation and the use of digital technology play an important role in attracting consumers, especially the younger generation. Apart from that, corporate social responsibility (CSR) is also a key factor in building a positive image of Islamic banks in society. This research suggests the need for public education, relevant product development, and regular evaluation of the marketing strategies implemented so that Islamic banking can develop sustainably.